EFFECT OF CAPITAL ADEQUACY ON THE FINANCIAL PERFORMANCE OF SAVINGS AND CREDIT SOCIETIES IN KENYA - Barus, Jane J.; Muturi, Dr. Willy; Kibati, Dr. Patrick; Koima, Dr Joel (American Journal of Finance, 2017)
Purpose: The purpose of this study to establish the effect of capital adequacy on the financial performance of savings and credit societies in Kenya. Methodology: The study employed an explanatory research design. The target population was 83 registered deposit taking SACCO's in Kenya that have been in operation for the last five years. The sample size for the study was all 83 SACCOs that have remained in existence since 2011-2015. Census methodology was used in the study. Both primary and secondary sources of data were employed. Multiple linear regression models were used to analyze the data using statistical package for the social sciences (SPSS) and STATA. A pilot study was conducted to measure the research instruments reliability and validity. Descriptive and inferential analysis was conducted to analyze the data. The data was presented using tables and graphs. Results: Based on the findings the study concluded that capital adequacy influenced the financial performance of savings and credit societies in Kenya. This can be explained by the regression results which showed that the influence was positive and also showed the magnitude by which capital adequacy influenced the financial performance of savings and credit societies. Unique contribution to theory, practice and policy: Based on the findings the study recommended for improvement of the capital requirement regulations by SASRA. The study also recommended that SACCO should improve their liquidity, profitability, operating efficiency and total assets turnover if they must remain in business and meet the capitalization threshold SASRA. Further, the study recommended that SACCO's should shift their concentration from increasing capital levels to credit risk management. Credit risk management would result to improvement in the financial performance of SACCO's.